2003
DOI: 10.1074/jbc.m301384200
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Heparin-binding Domains in the Triple-helical Domain of ColQ, the Collagen Tail Subunit of Synaptic Acetylcholinesterase

Abstract: ColQ, the collagen tail subunit of asymmetric acetylcholinesterase, is responsible for anchoring the enzyme at the vertebrate synaptic basal lamina by interacting with heparan sulfate proteoglycans. To get insights about this function, the interaction of ColQ with heparin was analyzed. For this, heparin affinity chromatography of the complete oligomeric enzyme carrying different mutations in ColQ was performed. Results demonstrate that only the two predicted heparin-binding domains present in the collagen doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…SMYD3 also upregulates genes linked to cell adhesion and invasion, such as ITGA5 [21] , COLQ [22] , SELL [23] , NEURL [24] , and PECAM1 [25] , which may be responsible for cell migration regulator y role of SMYD3 in our experiment. To investigate whether SMYD3 might act on HCC oncological activity through TSG inactivation, we examined if RIZ1 activity could be regulated by SMYD3 in different hepatoma cells.…”
Section: Discussionmentioning
confidence: 71%
“…SMYD3 also upregulates genes linked to cell adhesion and invasion, such as ITGA5 [21] , COLQ [22] , SELL [23] , NEURL [24] , and PECAM1 [25] , which may be responsible for cell migration regulator y role of SMYD3 in our experiment. To investigate whether SMYD3 might act on HCC oncological activity through TSG inactivation, we examined if RIZ1 activity could be regulated by SMYD3 in different hepatoma cells.…”
Section: Discussionmentioning
confidence: 71%
“…The GFP-ColQ-Y431S cDNA clone has been previously described by Cartaud et al (2004). The GFP-ColQ-⌬Ct and GFP-ColQ-⌬Col cDNA clones were generated from ⌬Ct and ⌬Col constructs described by Deprez et al (2003) in which the GFP tag sequence was introduced at the same position as for GFP-ColQ construct. The GFP-ColQ-⌬Col⌬Ct cDNA clone was generated by inserting four stop codons in the GFP-ColQ-⌬Col construct after the ColQ trimerization domain (amino acid 370).…”
Section: Methodsmentioning
confidence: 99%
“…First, MuSK-IgG does not block binding of ColQtailed AChE to the NMJ to a detectable extent in the patients. ColQ is localized to the synaptic basal lamina via 2 mechanisms: one is by binding to heparin sulfate proteoglycans including perlecan, 7,8 and the other is by binding to MuSK. 9 We previously reported that both mechanisms are required for in vitro anchoring of human ColQ to the frog NMJ.…”
Section: In Vitro Plate-binding Assay Shows That Musk-igg Blocks Bindmentioning
confidence: 99%
“…domain of ColQ 7 bind to heparin sulfate proteoglycans, such as perlecan 8 ; and the C-terminal domain of ColQ binds to MuSK. 9 Five percent to 15% of patients with myasthenia gravis (MG) carry antibodies against MuSK (MuSK-immunoglobulin G [IgG]).…”
mentioning
confidence: 99%